Human Metapneumovirus: An Emerging Respiratory Pathogen - Rajeswar Reddy Kasarla, (Janaki Medical College Journal of Medical Science, 2025)
A surge in cases of acute respiratory infections with human metapneumovirus (hMPV) in January 2025 has become a serious global health concern. The hMPV spread from an infected person to others through secretions from coughing and sneezing, close personal contact, such as touching or shaking hands, touching objects or surfaces that have the viruses on them then touching the mouth, nose, or eyes. The infections were usually mild, affecting infants, elderly or immunocompromised, and common in winter and early spring.  Early symptoms included runny nose, cough, and sore throat. Good hygiene practices, such as regular hand washing and avoiding close contact with infected individuals are important in prevention. There are many myths and misconceptions about hMPV infections. This review dives deep into the outbreak and discusses about the human metapneumovirus, and its transmission, clinical features, diagnosis, treatment and preventive measures, and attempts to dispel myths and create awareness among the public and healthcare providers.